1995
DOI: 10.1111/j.1365-2796.1995.tb00883.x
|View full text |Cite
|
Sign up to set email alerts
|

Diterpene composition of oils from Arabica and Robusta coffee beans and their effects on serum lipids in man

Abstract: Both Arabica and Robusta oil elevated serum lipid levels; therefore, cafestol must be involved and kahweol cannot be the sole cholesterol-raising diterpene. The mode of action of coffee diterpenes does not involve induction of hypothyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 24 publications
4
25
0
1
Order By: Relevance
“…Although no parallel placebo group was present in this study it is unlikely that such large responses of liver enzymes would be observed with placebo oil. This is supported by previous studies with coffee and placebo oil [1,9,25]. We found no correlation between the response of liver enzymes to coffee oil and baseline liver enzyme activities, serum lipid response, or alcohol.…”
Section: Discussionsupporting
confidence: 91%
“…Although no parallel placebo group was present in this study it is unlikely that such large responses of liver enzymes would be observed with placebo oil. This is supported by previous studies with coffee and placebo oil [1,9,25]. We found no correlation between the response of liver enzymes to coffee oil and baseline liver enzyme activities, serum lipid response, or alcohol.…”
Section: Discussionsupporting
confidence: 91%
“…These changes resemble those caused by diterpenes, but the levels of thyroxine, tri-iodothyronine and thyroid-stimulating hormone were all unaffected in 1 1 volunteers who took 2 g of coffee oil per day for 3 weeks, despite rises in LDL and VLDL cholesterol [33].…”
Section: E#ects On the Thyroidmentioning
confidence: 86%
“…It was shown that this effect is caused by the lipids present in the coffee brew, which, although poorly soluble in water, could be incorporated in the brew depending on the method of infusion. Initially, triglycerides were said to be responsible for this effect but in more recent years, it has been established that it is the diterpenes, especially cafestol and kahweol, both in free form and as palmitate esters which influence the serum cholesterol level (Bak and Grobbee, 1989;Weusten-Van der Wouw et al, 1994;Mensink et al, 1995;De Roos and Katan, 1999;Terpstra et al, 2000;Boekschoten et al, 2005). Other diterpenes have not been tested yet.…”
Section: Diterpenes In Coffee Beverages and Health Aspectsmentioning
confidence: 99%